Improving the Students' Reading Comprehension by Using Magazine at the First Grade Students of SMPN 2 Lasusua - Hijrah, Nur (USN Kolaka, 2022)
This study aimed to improve students’ reading comprehension through the use of magazines. The research was conducted at SMPN 2 Lasusua with 26 first-grade students as the subjects. The researcher employed a Classroom Action Research (CAR) design, implemented in two cycles, to enhance the learning process and students’ comprehension skills. Each cycle included planning, action, observation, and reflection stages. Data were collected using reading comprehension tests administered at the end of each cycle. The findings demonstrated a significant improvement in students’ reading comprehension scores across the two cycles. The average score increased from 61.1 in Cycle 1 to 83.3 in Cycle 2. This improvement was particularly evident in students’ ability to identify main ideas, a critical component of reading comprehension. Observation of classroom activities also indicated increased student engagement and motivation during learning sessions using magazines. The results suggest that incorporating magazines into reading instruction can serve as an effective pedagogical strategy for enhancing comprehension skills. The visual and contextual support provided by magazines helps students to connect text with real-life contexts, facilitating better understanding and retention of information. Based on these findings, it is recommended that English teachers integrate magazines as supplementary materials in reading lessons. Additionally, further research can explore the effectiveness of different types of magazines or other authentic materials to improve students’ higher-order reading skills. This study highlights the importance of active, student-centered approaches in fostering literacy and comprehension in secondary education.